2015
DOI: 10.3892/etm.2015.2858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhein lysinate on D-galactose-induced aging mice

Abstract: Abstract. The aim of the present study was to investigate the anti-aging effects of rhein lysinate (RHL), and to explore its mechanism of action in a D-galactose-induced aging mouse model. Aging was induced by D-galactose (100 mg/kg/day) that was subcutaneously injected to animals for 8 weeks. RHL was simultaneously administered once a day by intragastric gavage. The appetite, mental condition, body weight and organ index of the mice were monitored. Superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 47 publications
1
17
0
1
Order By: Relevance
“…The free radical theory poses that reactive oxygen species (ROS)-induced oxidative damage plays a requisite part in the pathophysiology of ageing 2 , 3 . Abundant evidence suggests that oxygen-derived free radicals are closely correlated to signal recognition, protein expression, and immune response.…”
Section: Introductionmentioning
confidence: 99%
“…The free radical theory poses that reactive oxygen species (ROS)-induced oxidative damage plays a requisite part in the pathophysiology of ageing 2 , 3 . Abundant evidence suggests that oxygen-derived free radicals are closely correlated to signal recognition, protein expression, and immune response.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the endogenous antioxidant enzyme system, mainly including SOD (an enzyme devoted to scavenge superoxide anion radicals and reduce the production of lipid peroxidation), CAT (an enzyme dedicated to scavenge H 2 O 2 to protect peroxidation of cell wall lipid and lipoproteins), and GSH-Px (an enzyme concentrated on catalyzing GSH into GSSG and stimulating the toxic peroxide reduction into non-toxic hydroxyl compounds), is an important defense system against free radical damage in the body, the main function of which is to maintain the homeostasis of ROS in the internal environment and to remove excessively high levels of ROS [ 4 , 5 , 32 , 33 ]. Numerous evidences exhibit that the excessive production of ROS in biological systems can cause oxidative damage to tissues, impair membrane functions, affect cellular metabolism, and passivate proteins and enzymes, especially in the organs with fast metabolic processes like the liver and kidney [ 34 , 35 , 36 ]. Consistent with these studies, we found that repeated d -gal-injection induced an observable decrease in the activities of these key antioxidant enzymes (SOD, CAT, and GSH-Px), and markedly aggravated lipid peroxidation, manifested as the accumulation of MDA, indicating that oxidative damages occurred in mice liver and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt1 may increase organismal longevity by tipping FOXO-dependent responses away from apoptosis and toward stress resistance [54]. Studies have found that Sirt1 expressions in the liver, kidney were decreased in D-gal-treated mice [55]. In addition, Glb1, which coding β-galactosidase, has been reported to increase during the replicative senescence of fibroblast cultures and has been used widely as a marker of cellular senescence in vivo and in vitro [56].…”
Section: Discussionmentioning
confidence: 99%